Measuring acceleration in the area of human head for energy harvesting purposes - Smilek, Jan; Cieslar, Filip; Hadas, Zdenek (2016 17th International Conference on Mechatronics - Mechatronika (ME), 2016)
This paper deals with measurements and statistical processing of the acceleration data measured in the area of the human head. Kinetic energy harvesters require such levels of acceleration for their excitation that could possibly be obtained from human movements. 30 different people with different characteristics were thus measured during walking at controlled speeds in order to find the common frequencies and relevant magnitudes in the acceleration waveforms. Different ways of mounting the accelerometer to the head are also presented and the measurement results compared to identify and filter out the parasitic acceleration frequencies.